Post-COVID-19 Syndrome and Related Dysautonomia: Reduced Quality of Life, Increased Anxiety and Manifestation of Depressive Symptoms: Evidence from Greece - Galanis, Petros; Katsiroumpa, Aglaia; Vraka, Irene; Kosiara, Katerina; Siskou, Olga; Konstantakopoulou, Olympia; Katsoulas, Theodoros; Gallos, Parisis; Kaitelidou, Daphne (Acta medica Lituanica, 2023)
Background: Post-COVID-19 syndrome affects a significant number of SARS-CoV-2 infected individuals, even in asymptomatic cases causing several neurological and neuropsychiatric symptoms and signs.Materials and Methods: An online cross-sectional study with a convenience sample was conducted in Greece from November 2022 to January 2023. We measured the demographic and clinical characteristics of patients with post-COVID-19 dysautonomia in terms of the quality of life with the EQ-5D-3L, and anxiety and depressive symptoms by employing Patient Health Questionnaire-4.Results: The study population included 122 patients with post-COVID-19 syndrome. One out of four patients (27.8%) manifested post-COVID-19 dysautonomia, while the mean duration of COVID-19 symptoms was 11.6 months. Anxiety and depressive symptoms were worse after the post-COVID-19 syndrome (p
Keywords: post-COVID-19 syndrome; dysautonomia; anxiety; depression; quality of life